Theodor Adorno and Anglophone modernist literature - Hingley, L (2021)
Though studies of Adorno and literature have proliferated over the last 15 years, Adorno’s engagement with Anglophone literature continues to be overlooked. This thesis seeks to remedy such an omission by outlining the importance of four Anglophone writers - Dickens, Joyce, Beckett and Huxley - to Adorno’s wider philosophical project. I show how Adorno drew upon these writers’ works and interpreted them in his own specific way as modernist texts – in other words, as texts that had an especially critical, cognitive quality that would allow him to discuss and potentially counteract the false consciousness promoted by the different stages of capitalism. In the first chapter, I establish how Adorno uses Dickens’ novel The Old Curiosity Shop to propose a specific theory of allegory to resist reification in capitalist society. In the second chapter, I argue that Adorno should be understood as giving a powerful but tendentious reading of Joyce’s novels Ulysses and Finnegans Wake. In the third chapter, I uncover how Beckett’s The Unnamable and Endgame offer a paradoxical form of therapy for Adorno: their redemptive potential stems from their self-conscious failure to be consolatory texts. In the fourth and final chapter, I demonstrate how Adorno sees Huxley’s Brave New World as a tool for resisting the culture industry’s false consciousness because it promotes a kind of pleasure that opposes the false pleasures of capitalism. Overall, I aim to show the key role that Anglophone literature had in Adornian thought; it was both the source and object of his critical theory as well as a space that exposed the limits of its very place within his philosophy.